A multi-national validity analysis of the Personal Report of Communication Apprehension (PRCA-24). Issue 3 (3rd July 2019) - Croucher, Stephen M.; Kelly, Stephanie; Rahmani, Diyako; Jackson, Kelsea; Galy-Badenas, Flora; Lando, Agnes; Chibita, Monica; Nyiranasbimana, Venantie; Turdubaeva, Elira; Eskiçorapçı, Nadirabegim; Condon, Shawn Michael; Stanalieva, Gulzada; et al.
ABSTRACT: Methodological issues abound when conducting cross-cultural research. In this manuscript we discuss three methodological issues present in many cross-cultural communication studies: lack of geographic diversity, reliability, and validity. To explore these issues the Personal Report of Communication Apprehension (PRCA-24) is assessed. The PRCA-24 serves as an exemplar of a US-designed and -validated measure frequently used outside the US without tests of validity or measurement invariance. In fact, since 1990 less than 10 studies have reported validity results, often citing fit issues. The PRCA-24 was administered to respondents from 11 countries and failed to yield acceptable fit statistics in all samples, showing poor construct validity. Implications for cross-cultural research are discussed, with particular emphasis on recommendations for increased cross-cultural methodological rigor.